2010
DOI: 10.1128/jvi.02408-09
|View full text |Cite
|
Sign up to set email alerts
|

A Detrimental Effect of Interleukin-10 on Protective Pulmonary Humoral Immunity during Primary Influenza A Virus Infection

Abstract: Interleukin-10 (IL-10) is an important anti-inflammatory molecule that can cause immunosuppression and long-term pathogen persistence during chronic infection of mice with viruses such as lymphocytic choriomeningitis virus. However, its specific role in immunity to acute viral infections is not fully understood. We found that IL-10 plays a detrimental role in host responses to acute influenza A virus since IL-10 ؊/؊ mice had improved viral clearance and survival after infection compared to wild-type mice. Enha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
89
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(93 citation statements)
references
References 20 publications
3
89
1
Order By: Relevance
“…In support of this, HSV-1 infection has been shown to induce CXCL9 expression, as shown here and in earlier studies (43). Collectively, these observations suggested that CXCL9 played opposing roles in HSV-1 virulence in the CNS, probably depending on the quantity and/or timing of CXCL9 expression during the infection, just like other cytokines such as IL-10 do in other viral infections (44,45). Therefore, HSV-1 needs to tightly regulate CXCL9 expression, and thus has evolved to express UL13 as regulator of CXCL9.…”
Section: Discussionsupporting
confidence: 57%
“…In support of this, HSV-1 infection has been shown to induce CXCL9 expression, as shown here and in earlier studies (43). Collectively, these observations suggested that CXCL9 played opposing roles in HSV-1 virulence in the CNS, probably depending on the quantity and/or timing of CXCL9 expression during the infection, just like other cytokines such as IL-10 do in other viral infections (44,45). Therefore, HSV-1 needs to tightly regulate CXCL9 expression, and thus has evolved to express UL13 as regulator of CXCL9.…”
Section: Discussionsupporting
confidence: 57%
“…Using a similar model, another study concluded that memory CD4 + T cell protection is dependent on IFN-γ and that the protective capacity of these cells remains robust in lymphocyte-deficient hosts (12). However, this study was largely restricted to monitoring the first week of infection, and the importance of IFN-γ in protection against IAV remains controversial, with diverse reports citing either no role (2,(13)(14)(15)(16)(17) or a critical contribution (17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
“…In experimental mice, IL-10 seems to aggravate the disease. IL-10 knockout (KO) mice survive better than wild-type (WT) mice upon infection with influenza virus 21,22 . However, IL-10 receptor (IL-10R) blockade after 3 days of infection increases mortality with aggravated pulmonary inflammation in mice 19 .…”
mentioning
confidence: 99%